PENETAPAN MAHAR TERHADAP KELANGSUNGAN PERNIKAHAN DITINJAU MENURUT HUKUM ISLAM - Putra Halomoan (Institut Agama Islam Negeri Batusangkar, 2016)
In Islamic marriage system, mahar is one of the prior concern although it is not any of rules (rukun) of the marriage itself. Etymologically, mahar means dowry. Terminologically, it refers to something which is given by a husband to his wife as replacement or guarantee from him from what he takes from her. It can be either in form of things or sevices (such as setting slaves free, teaching, etc. Basically, mahar is genuinely the right of a wife. That means it is the wife that determines what and how many/much she wants it to be given to her. Even if she does not want anything for her mahar, a husband does not need to force to provide it. However, if his wife requires him to give her mahar, it should be whole and kind hearted gift to her. This reasonable since mahar symbolizes deep and true feeling of love and legal evidence of bond between a husband and a wife. However, in its implementation, mahar is not a simple as it may seem. Involving traditional and religious leaders in determining and approving mahar (as in Binabo Julu village) made few marriages postponed, unregistered (siri) or even cancelled. This also indicates that mahar potentially gives unexpected impacts toward the marriage it selfKata kunci: mahar, pernikahan, dan hukum Islam